1990
DOI: 10.1042/cs0790451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Ethanol Administration and its Withdrawal on the Level and Binding of Somatostatin in Rat Brain

Abstract: 1. Acute ethanol administration resulted in an increase in the total number of specific somatostatin receptors in rat frontoparietal cortex and hippocampus, and a decrease in the level of somatostatin-like immunoreactivity in the hippocampus but not in the frontoparietal cortex. 2. Chronic administration of ethanol caused a decrease in the number of somatostatin receptors in the frontoparietal cortex but not in the hippocampus, although the level of somatostatin-like immunoreactivity was unchanged in both brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…However, chronic ethanol ingestion in virgin rats had no effect on SRIF content when compared with control virgin rats. These results are in agreement with our previous results in male rats (Barrios et al, 1990). In vitro studies have demonstrated that chronic ethanol treatment has no direct effect either on SRIF content or SRIF mRNA levels in neurons (Rage et al, 1998) and in vivo results suggest that a much longer period of alcohol consumption is necessary to diminish brain SRIF content in non-pregnant rats (Madeira et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, chronic ethanol ingestion in virgin rats had no effect on SRIF content when compared with control virgin rats. These results are in agreement with our previous results in male rats (Barrios et al, 1990). In vitro studies have demonstrated that chronic ethanol treatment has no direct effect either on SRIF content or SRIF mRNA levels in neurons (Rage et al, 1998) and in vivo results suggest that a much longer period of alcohol consumption is necessary to diminish brain SRIF content in non-pregnant rats (Madeira et al, 1997).…”
Section: Discussionsupporting
confidence: 83%
“…We have shown that on the day of delivery, there is an increase in the number of SRIF receptors in the frontoparietal cortex of rat dams (Barrios et al, 1993). Since SRIF increases locomotor activity in the rat (Justino et al, 1997) and chronic ethanol ingestion decreases the number of SRIF receptors in the rat frontoparietal cortex (Barrios et al, 1990), we hypothesized that the SRIFergic system could be implicated, at least partly, in the decrease of motor activity found in parturient rats that have consumed ethanol during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that SST signaling is involved in several key processes in SUD (for review see Robinson and Thiele (2020) ). Preclinical studies suggest that SST signaling is involved in regulating several reward-related behaviors including food intake and cocaine and alcohol consumption ( Fuhrmann et al, 1986 ; Mancillas et al, 1986 ; Barrios et al, 1990 ; Andrade et al, 1992 ; Yuferov et al, 2003 ; Stengel et al, 2010b ). SST administration increases dopamine release in the striatum ( Hathway et al, 1998 ) and SST and SST receptor expression is altered in several brain regions including the hippocampus following exposure to alcohol or cocaine ( Fuhrmann et al, 1986 ; Mancillas et al, 1986 ; Barrios et al, 1990 ; Andrade et al, 1992 ; Yuferov et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies suggest that SST signaling is involved in regulating several reward-related behaviors including food intake and cocaine and alcohol consumption ( Fuhrmann et al, 1986 ; Mancillas et al, 1986 ; Barrios et al, 1990 ; Andrade et al, 1992 ; Yuferov et al, 2003 ; Stengel et al, 2010b ). SST administration increases dopamine release in the striatum ( Hathway et al, 1998 ) and SST and SST receptor expression is altered in several brain regions including the hippocampus following exposure to alcohol or cocaine ( Fuhrmann et al, 1986 ; Mancillas et al, 1986 ; Barrios et al, 1990 ; Andrade et al, 1992 ; Yuferov et al, 2003 ). Furthermore, recent findings demonstrate a key role for SST signaling in the hippocampus in regulating memory consolidation during sleep ( Delorme et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%